Pengaruh Investasi Pemerintah Dalam Bentuk Pembangunan Infrastruktur Terhadap Kesempatan Kerja di Provinsi sumatera Utara - Muhammad Yunus Sofian; Ryan Arianda; Nurul Jannah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Investment is a commitment or decision regarding several funds, as well as other aspects that are carried out and started in the present, but the benefits are expected to be obtained in the future. This investment can also be related to various activities. Government investment means that the central government invests various funds and commodities to invest in long-term purchases of securities and assets. This research was created and conducted through quantitative descriptive research. The purpose of this study is to analyze the impact of national investment in the form of infrastructure expansion on the unemployment rate and income of the population of North Sumatra. In general, the existing infrastructure development in North Sumatra has significantly reduced the unemployment rate in North Sumatra. Investment in the form of infrastructure development has a positive, but not significant impact on job opportunities in North Sumatra Province. The increase or decrease in the value of the incoming investment does not significantly affect the increase in the percentage of employment opportunities in North Sumatra.